Factor of communication barrier that influence workers productivity in oil palm plantation sector / Ahmad Aslah Azriq Ahmad Aspi - Ahmad Aspi, Ahmad Aslah Azriq (Faculty of Plantation and Agrotechnology, 2018)
Human interacting with each other can also be known as form of communication. Effectively communicating with employers, employees, clients, suppliers, and customers will help you succeeds in this business world (Shonubi & Akintaro, 2016). Most of successful business people in the world are the one that have good communication skill. Aim of this study is to investigate relationship factor of communication barrier toward the productivity of workers based on five factors which are physical barrier, language barrier, perceptual barrier, gender barrier and emotional barrier. A method for this research is survey by using questionnaires and the study location at Lembah Kesang Estate. Total respondent for this research are 52 respondents. Statistical Package for Social Science (SPSS) consist of correlation coefficient and multiple regression is been used to analyzed all the data recorded. Result shows that gender barrier give the highest positive relationship (0.556) on the productivity of workers. As for the recommendation, estate workers need to remove their stereotype toward the woman employee in oil palm plantation sector to achieve effective communication.